ANALYSIS OF CUSTOMER SATISFACTION USING IMPORTANCE PERFORMANCE ANALYSIS (IPA) METHOD AT HOUSE OF TJIHAPIT - Kayla Vania Ayu Tjandra; Ganjar Mohamad Disastra (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study uses the Importance-Performance Analysis (IPA) method to evaluate the service quality at the House of Tjihapit, a restaurant in Bandung that faces challenges due to the COVID-19 pandemic. A quantitative approach was applied, gathering data through questionnaires to assess customer expectations and perceptions of service performance. The findings reveal that while overall service performance slightly exceeds customer expectations by 2%, issues such as poor handling of service problems remain. The study concludes that despite satisfactory service quality, there is a need for targeted improvements in specific areas to enhance customer satisfaction and retention. Future research should explore similar evaluations across multiple venues to provide a broader understanding of service quality in the industry. Keywords: Service Quality; Customer Satisfaction; Importance-Performance Analysis